2020
DOI: 10.1007/s12648-020-01731-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Landau damping on ion acoustic solitary waves in a collisionless unmagnetized plasma consisting of nonthermal and isothermal electrons

Abstract: A Korteweg-de Vries (KdV) equation including the effect of Landau damping is derived to study the propagation of weakly nonlinear and weakly dispersive ion acoustic waves in a collisionless unmagnetized plasma consisting of warm adiabatic ions and two different species of electrons at different temperatures. The hotter energetic electron species follows the nonthermal velocity distribution of Cairns et al. [Geophys. Res. Lett. 22, 2709 (1995)] whereas the cooler electron species obeys the Boltzmann distributio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Based on wave-particle response interactions used to modify the shape of the solution a detailed study was proposed, as it was observed, these interactions in the plasma lead to the acceleration of charged particles as a result of the transfer of wave energy to these particles 19 . Recently, experimental results have predicted the formation of acoustic ion shock waves due to the dissipation caused by Landau damping 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Based on wave-particle response interactions used to modify the shape of the solution a detailed study was proposed, as it was observed, these interactions in the plasma lead to the acceleration of charged particles as a result of the transfer of wave energy to these particles 19 . Recently, experimental results have predicted the formation of acoustic ion shock waves due to the dissipation caused by Landau damping 20 .…”
Section: Introductionmentioning
confidence: 99%